2014
DOI: 10.1101/cshperspect.a020644
|View full text |Cite
|
Sign up to set email alerts
|

The Genesis of Tyrosine Phosphorylation

Abstract: Tyrosine phosphorylation of proteins was discovered in 1979, but this posttranslational modification had been "invented" by evolution more than a billion years ago in singlecelled eukaryotic organisms that were the antecedents of the first multicellular animals. Because sophisticated cell -cell communication is a sine qua non for the existence of multicellular organisms, the development of cell-surface receptor systems that use tyrosine phosphorylation for transmembrane signal transduction and intracellular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 65 publications
(66 reference statements)
1
133
0
3
Order By: Relevance
“…They have provided the basis for understanding (1) the requirement for dimerization for kinase activation, and (2) the mechanism of transphosphorylation (Shibuya 2013;Song et al 2013;Barton et al 2014;Hunter 2014). The first crystal structures of the liganded ErbB1 receptor (Garrett et al 2002;Ogiso et al 2002) revealed an extended extracellular structure with ligand binding between domains 1 and 3 and dimerization through domain 2, confirming an earlier model of Lemmon et al (1997) of two EGF:two ErbB1 receptors.…”
Section: What Is the Structure Of The Erbb1 In Living Cells?supporting
confidence: 61%
“…They have provided the basis for understanding (1) the requirement for dimerization for kinase activation, and (2) the mechanism of transphosphorylation (Shibuya 2013;Song et al 2013;Barton et al 2014;Hunter 2014). The first crystal structures of the liganded ErbB1 receptor (Garrett et al 2002;Ogiso et al 2002) revealed an extended extracellular structure with ligand binding between domains 1 and 3 and dimerization through domain 2, confirming an earlier model of Lemmon et al (1997) of two EGF:two ErbB1 receptors.…”
Section: What Is the Structure Of The Erbb1 In Living Cells?supporting
confidence: 61%
“…This latter group is of special interest in the context of signal transduction, as exemplified by the pTyr-interacting Src homology 2 (SH2) domains [66,67]. In fact one of the most important functions of phosphotyrosine (pTyr) is to act as a docking site that mediates specific interactions between the phosphoprotein and another protein (or region of the same protein) that contains a pTyr-binding domain, such as SH2 or phosphotyrosine binding (PTB) (for review [68,69]). As far as pSer/pThr is concerned the first binding proteins to be identified were the so called 14-3-3 proteins [70], which tightly regulate G2-M progression through a series of interactions with the mitotic regulatory tyrosine phosphatase Cdc25 [71,72].…”
Section: Phosphotyrosine Comes Into the Scenementioning
confidence: 99%
“…[80][81][82] If one embraces Julian's idea of antibiotics as mediators of cell-cell communication, it is interesting also to consider aminoglycoside phosphotransferases potentially serving as modulators of such signaling pathways-much as kinases that act on key regulatory proteins can profoundly alter cellular and developmental signaling networks. [83][84][85][86] Julian's challenge to us, to rethink just what roles antibiotics may play in Nature, illustrates yet once again his creativity, his clarity of thought, his biochemical and evolutionary insights, and why it was such an immense pleasure and privilege to work with him in Geneva and Madison some four decades ago.…”
Section: Aminoglycosides Sequence Relationships Of Their Phosphotranmentioning
confidence: 99%